Concerted transfer of the virulence Ti plasmid and companion At plasmid in the Agrobacterium tumefaciens‐induced plant tumour. Issue 6 (31st October 2013) - Lang, Julien; Planamente, Sara; Mondy, Samuel; Dessaux, Yves; Moréra, Solange; Faure, Denis
Summary The plant pathogen Agrobacterium tumefaciens C58 harbours three independent type IV secretion (T4SS) machineries. T4SST‐DNA promotes the transfer of the T‐DNA to host plant cells, provoking tumour development and accumulation of opines such as nopaline and agrocinopines. T4SSpTi and T4SSpAt control the bacterial conjugation of the Ti and At plasmids respectively. Expression of T4SSpTi is controlled by the agrocinopine‐responsive transcriptional repressor AccR. In this work, we compared the genome‐wide transcriptional profile of the wild‐type A. tumefaciens strain C58 with that of its accR KO‐mutant to delineate the AccR regulon. In addition to the genes that encode agrocinopine catabolism and T4SSpTi, we found that AccR also regulated genes coding for nopaline catabolism and T4SSpAt. Further opine detection and conjugation assays confirmed the enhancement of nopaline consumption and At plasmid conjugation frequency in accR. Moreover, co‐regulation of the T4SSpTi and T4SSpAt correlated with the co‐transfer of the At and Ti plasmids both in vitro and in plant tumours. Finally, unlike T4SSpTi, T4SSpAt activation does not require quorum‐sensing. Overall this study highlights the regulatory interplays between opines, At and Ti plasmids that contribute to a concerted dissemination of the two replicons in bacterial populations colonizing the plant tumour.